EVALUASI DAN OPTIMASI SIMPANG BANGKONG DAN MILO KOTA SEMARANG - Marlina Julianti; Prima Setiadita; Bambang Pudjianto; Djoko Purwanto (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
Semarang city as a big city develop rapidly as centre business, trade, and government in Central Java faced with transportation problems such as traffic congestion caused by the volume of road vehicles with the road capacity is not balanced. The result of analysis of existing conditions with reference, Bangkong Intersection dominant currents in the western and eastern approach that shows the performance of intersections with an average degree of saturation 1,218 that means in excess of the ideal number. In the eastern approach Bangkong Intersection in the peak of morning, afternoon and evening, long queue reached 95 m, 219 m, and 219 m. To value the average intersection delay 62.46 sec/smp , 235.24 sec/smp, and 137.68 sec/smp. While in Milo Intersection, average DS values 1,100 that means in the excess of the ideal number. Long queues at the eastern approach Milo Intersection in the peak morning, afternoon and evening is 108 m, 242 m, and 242 m. To value the average intersection delay with a value of 36.99 sec/smp, 65.39 sec/smp, and 108.16 sec/smp.To get the operation optimization Simpang Bangkong and Milo made simulations by showing 3 scenarios. It was made the scenario 1 is the green time adjustments resulting DS same value in every second approach the intersection. Scenario 2 is to change LTOR into LT with the result being a greater capacity, the DS becomes small, a larger queue length, and delay be small. Next, scenario 3 is made by changing into a one-way system. Here after devised scenario 3, is one way system to produce a DS value becomes smaller, a small queue length, delay values are relatively larger. For QL values obtained Bangkong Intersection 44 m, 40 m, and 99 m. the average of intersection delay values 46.88 sec/smp, 38.27 sec/smp , and 40.74 sec/smp. For Milo Intersection, the value of QL is 27, 15 m, and 18 m. Value of the average intersection delay 8.81 sec/smp, 32.60 sec/smp , and 7.61 sec / smp. The results of the analysis with 3 scenarios show that one way system scenario has better performance with consideration of this scenario prioritize large traffic flow from west to east and toward the opposite.